Performance of Commercai Banks of Pakistan in the backdrop of Global Financial Crisis (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
This research paper highlights the efficiency & performance of commercial banks of Pakistan after the emergence of global financial crisis. The crisis were basically started in United States after the collapse of subprime mortgage market but engulfed the entire globe though the level of severity was different from country to country. Paper also discusses the challenges and obstacles hindered the smooth performance of banking sector in Pakistan. Five big banks of the country were selected to evaluate their efficiency in terms of profits, liquidity and solvency.For this purpose various financial ratios were used to avoid size disparity of banks. The banks play an important role of financial intermediation; channelize savings of public to investors hence basic key performance indicators for this research were deposits, profit, advances and capital.An attempt has been made to examine the growth and sustainability of banks through their performance from 2007 to 2012, before and after crisis.The main findings are (I) the profitability was affected adversely (II) Non Performing Loans were increasedsignificantly after tight control and management for several years.(III) It was explored that costly deposits were mobilized to maintain the book size and restore the confidence of depositors and all stake holders. (IV)The stability of the system remained unquestionable due to maintenance of Capital Adequacy Ratio well above the targeted ratio of 8 % in terms of Basel accord.